FINANCIAL LOSS RISK MODELLING DUE TO TECTONICEARTHQUAKES USING EARTHQUAKE CATASTROPHE(CAT) MODEL: CASE STUDY OF RESIDENTIAL BUILDINGIN KOTA SORONG, SOUTHWEST PAPUA REGENCY - Fauzan Rahmady, Muhammad
Indonesia is at a meeting point of four major plates in the world, namely: the Eurasia, the Pacific, the Indo-Australian, and the Philippine Sea Plates. This makes Indonesia very vulnerable to the risks of earthquakes catastrophe events, both tectonic and volcanic. Apart from causing casualties, tectonic and volcanic earthquakes could also result in financial losses due to damages on properties and infrastructures. In this final project, a methodology for modeling financial losses caused by tectonic earthquakes is discussed by using an Earthquake Catastrophe (CAT) Model. OpenQuake is a software, developed by the Global Earthquake Model (GEM), to build a CAT model using synthetic earthquake catalogs. As a comparison, in this Final Project, an Event Loss Table (ELT) is constructed based on the probability distribution of the moment magnitude mainshocks of tectonic earthquakes in some megathrusts. Specifically, the ELTs constructed are to model the financial losses suffered by residentials in Kota Sorong, Southwest Papua Province. The financial losses are modeled using the Collective Risk model; and the Monte-Carlo simulations are used to generate several ELTs. From the resulting ELTs, the Value-at-Risk and the corresponding Tail Value-at-Risk are used to measure the risks of financial losses suffered by residentials in Sorong City, Southwest Papua Province.